Upaya Peningkatan Melek Tekhnologi dan Administrasi melalui Program Kampus Mengajar pada SDN Banjarsari 04 Kabupaten Jember - Abdurahman Abdurahman; Shevira Desty Ramadhani; Heru Wahyudi (Yumary: Jurnal Pengabdian kepada Masyarakat, 2023)
Purpose: Students are expected to be able to improve the quality of education in schools and can have a real impact on student progress in terms of technology, administration, literacy and numeracy. Research methodology: Classroom teaching activities, helping to improve school administration, helping to adapt school technology, carrying out special guidance to improve the spirit of student nationalism, cultivating literacy before learning and improving social spirit Results: As much as 85% are able to use good technology while for the implementation of school administration it is in accordance with the achievement of the objectives Conclusion: Students are able to help students to be able to use existing technology well and in the implementation of school administration there has been significant progress. Limitation: The limitation of this service is the implementation time. Contribution: This technology can help expand the knowledge of students and teachers.